2007
DOI: 10.1111/j.1524-4725.2007.33257.x
|View full text |Cite
|
Sign up to set email alerts
|

The Use of High-Frequency Ultrasound in the Evaluation of Superficial and Nodular Basal Cell Carcinomas

Abstract: HFUS delineated tumor margins adequately, and it appeared to depict subclinical extension past 4 mm on less aggressive BCC variants. It could be warranted if clinical or histologic diagnosis is uncertain. The strong association between clinical and ultrasonic measurements initiates more successful forms of therapy, risk-stratifies specific subgroups of patients, and prevents overall morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(82 citation statements)
references
References 24 publications
1
79
0
2
Order By: Relevance
“…One recent publication correlated the ultrasonographic assessment of superficial and nodular BCCs with the histopathological measurements of the tumors postexcision (with fixed 4-mm margins), determining that HFUS was able to accurately predict which tumors had subclinical extension beyond 4-mm margins in 48 of 50 cases. 20 The remaining two tumors were determined to be infiltrative and morpheaform and were not able to be properly outlined using HFUS technology. Another study, examining the role for HFUS in improving the surgical precision of Mohs micrographic surgery for NMSC (regardless of histologic subtype), found that HFUS was more sensitive in determining subclinical extension of larger ([1.74 cm 2 ) tumors but was not adequately sensitive in picking up more subtle areas of extension in smaller and more insidious tumors.…”
Section: Skin Cancermentioning
confidence: 99%
“…One recent publication correlated the ultrasonographic assessment of superficial and nodular BCCs with the histopathological measurements of the tumors postexcision (with fixed 4-mm margins), determining that HFUS was able to accurately predict which tumors had subclinical extension beyond 4-mm margins in 48 of 50 cases. 20 The remaining two tumors were determined to be infiltrative and morpheaform and were not able to be properly outlined using HFUS technology. Another study, examining the role for HFUS in improving the surgical precision of Mohs micrographic surgery for NMSC (regardless of histologic subtype), found that HFUS was more sensitive in determining subclinical extension of larger ([1.74 cm 2 ) tumors but was not adequately sensitive in picking up more subtle areas of extension in smaller and more insidious tumors.…”
Section: Skin Cancermentioning
confidence: 99%
“…It is usually well delimited from the surrounding dermis.Ultrasound may also assist the detection of early recurrence, especially when surgical removal is incomplete or in cases treated with radiotherapy or cryosurgery. Ultrasound may also be used to help to determine the surgical margins or to delimitate the area treated with radiotherapy or cryosurgery (25,(27)(28)(29)(30)(31)(32). This may decrease the rate of relapse.…”
Section: Basal Cell Carcinoma (Bcc)mentioning
confidence: 99%
“…The influence of cells on the refractive qualities of the tissue may be analogous to the situation when using ultrasound. It is well known from high-frequency ultrasound imaging that inflammation surrounding BCC has the same echogenecity as tumor cells [28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%